2020
DOI: 10.1371/journal.pone.0231076
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Compliance in older age patients with chronic heart failure

Abstract: The purpose of the study was to evaluate compliance with medical treatment in elderly patients with heart failure (HF), and to identify factors that associated with patients' compliance levels. Methods and results 475 patients (including 222 women), mean age 69.7±7.7, with HF, hospitalized at University Hospital between January and December 2018 were included in the study. The patients were selected by a physician specializing in cardiology. A cardiac nurse assessed the non-pharmacological level of compliance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 40 publications
3
34
2
2
Order By: Relevance
“…Another predictor of lower intentional non-adherence levels in our study was being single, which is more commonly reported as a determinant of unintentional non-adherence, associated with a lack of motivation to follow treatment recommendations [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another predictor of lower intentional non-adherence levels in our study was being single, which is more commonly reported as a determinant of unintentional non-adherence, associated with a lack of motivation to follow treatment recommendations [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective self‐care, including symptom monitoring, regular exercise, sodium restriction and weight control, is a key component of HF management to improve the patient's prognosis (Herber et al, 2018; Jankowska‐Polanska et al., 2020). Recent studies have reported that self‐care behaviours can improve the health status and quality of life of patients with HF and reduce readmission and mortality rates (Beckie, Campbell, Schneider, & Macario, 2017; Lei & Cai, 2018; Toukhsati et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that self‐care behaviours can improve the health status and quality of life of patients with HF and reduce readmission and mortality rates (Beckie, Campbell, Schneider, & Macario, 2017; Lei & Cai, 2018; Toukhsati et al., 2019). Unfortunately, patients with HF feel that self‐care is difficult because of the multiple requirements of treatment regimens, such as polypharmacy and lifestyle adjustments for multimorbid conditions (Jankowska‐Polanska et al, 2020; Uchmanowicz, Jankowska‐Polańska, Mazur, & Froelicher, 2017). Older adults with HF are less likely to adhere to self‐care behaviours than younger patients are (Cocchieri et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure (HF) is a significant global health issue and disproportionately influences older individuals [ 1 , 2 , 3 ]. Older patients are liable to developing HF because of age-related physiologic and pathologic changes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%